1999
DOI: 10.1021/ja9921165
|View full text |Cite
|
Sign up to set email alerts
|

Nitrosation of 1,2-Phenylenediamine by Peroxynitrite/CO2:  Evidence for a Free Radical Mechanism

Abstract: Nitric oxide and S-nitrosothiols function as critical signaling species. 1 S-Nitrosothiols have a longer half-life 2 than does • NO, and typical concentrations of S-nitrosothiols in blood plasma are 3-4 orders of magnitude higher than those of • NO. 3 Thus, nitrosation can lead to the formation of S-nitrosothiols, which can serve as carriers of • NO; however, since • NO itself does not nitrosate, 4 the mechanism by which nitrosation occurs in vivo is still unclear. 5 We have recently shown that peroxynitrite (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 16 publications
5
34
0
Order By: Relevance
“…DAF-2; Kojima et al, 1998) or their rhodamine analoges (Kojima et al, 2001) all require prior activation by nonspecific oxidants before reaction with NO . Thus, all these share a common reaction scheme in which a fluorescent triazole is eventually formed from NO , but requires an obligate anilyl radical intermediate ( Figure 3) (Uppu and Pryor, 1999). This intermediate can obviously be formed from a wide variety of radical and enzyme-based oxidants, the levels of which will modulate the signal (Jourd'heuil, 2002).…”
Section: Oxidation and Nitration Initiated By Superoxide ( O 2 à ) Anmentioning
confidence: 99%
“…DAF-2; Kojima et al, 1998) or their rhodamine analoges (Kojima et al, 2001) all require prior activation by nonspecific oxidants before reaction with NO . Thus, all these share a common reaction scheme in which a fluorescent triazole is eventually formed from NO , but requires an obligate anilyl radical intermediate ( Figure 3) (Uppu and Pryor, 1999). This intermediate can obviously be formed from a wide variety of radical and enzyme-based oxidants, the levels of which will modulate the signal (Jourd'heuil, 2002).…”
Section: Oxidation and Nitration Initiated By Superoxide ( O 2 à ) Anmentioning
confidence: 99%
“…Regardless of the mechanism involved, the images obtained in this study with broadly-distributed NO sources serve as a vivid reminder that fluorescence DAF-2 T patterns do not necessarily correlate with local NO production. This issue is further complicated by the finding that DAF-2 is subject to oxidation to a radical cation that can directly trap NO [64,65].…”
Section: Is Daf-2 Compartmentalized In Tissues?mentioning
confidence: 99%
“…These new findings add to the growing body of knowledge on how to best optimize their use [9,10] and avoid potential pitfalls [62][63][64][65][66], which will ultimately help investigators to use this relatively new class of fluorophores more judiciously for the investigation of NO-related events.…”
mentioning
confidence: 99%
“…33 These data can justify also the strong protection effect, almost against free radicals, of MLT on cell membranes, that have been reported. [4][5][6][7][8] Infrared spectra on the solid complex demonstrated that in the formation of inclusion complexes an important contribution is due to polar bonds formation-modification, thus evidencing once more 33 that MLT is preferentially localised in interfacial nano-districts, between polar and apolar domains. In these interfacial regions MLT can strongly act as protective agent.…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin has also recently come to footlights because it is the unique hormone which, being a strong antioxidant, can act as powerful inhibiter of free radicals, 3 scavenger of hydroxyl radicals, 4 lipoperoxyl radicals 5,6 and nitric oxide. 7,8 At present, therapeutic applications of melatonin include circadian rhythm disorders, 2 cancer, 9-11 AIDS, 12 Alzheimer disease, 13,14 cataract 15 and cardiac disease. 16 Further, for its relevant biological properties that are also associated with an extremely low toxicity, melatonin could act as a drug for a number of other diseases.…”
Section: Introductionmentioning
confidence: 99%